Reactive molten-flux assisted syntheses of single crystals of Cs19Ln19Mn10Te48 (Ln = Pr and Gd) crystallizing in a new structure type. Issue 47 (15th November 2021) - Panigrahi, Gopabandhu; Jana, Subhendu; Narayanswamy, S.; Bhattacharjee, Pinaki P.; Niranjan, Manish K.; Prakash, Jai
Abstract : Two new complex layered quaternary tellurides, Cs19 Ln19 Mn10 Te48 (Ln = Pr and Gd), were synthesized by the reactive molten flux method. The title compounds represent an unprecedented structure type. Abstract : Two new quaternary tellurides, Cs19 Ln19 Mn10 Te48 (Ln = Pr and Gd), were synthesized by the reactive molten-flux method at 1273 K using an excess of CsCl as a reactive flux. The single-crystal X-ray diffraction studies reveal that these compounds are isostructural and crystallize in a new structure type in the space group C 32h– C 2/ m of the monoclinic crystal system with two formula units. There are forty-nine unique crystallographic sites in the unit cell of the structure: ten Cs sites, ten Ln sites, five Mn sites, and twenty-four Te sites. All atoms have a site symmetry of . m . except for Cs(10) and Ln(10), which have a site symmetry of 2/ m . The unique crystal structure of Cs19 Ln19 Mn10 Te48 consists of complex layers of 2∞[Ln19 Mn10 Te48 ] 19− that are separated by filling of Cs + cations between the layers. The Ln atoms are bonded to six Te atoms that form a distorted octahedral geometry around the central Ln atom, whereas Mn atoms are coordinated to four Te atoms in a distorted tetrahedral fashion. The building blocks of these structures (LnTe6 octahedra and MnTe4 tetrahedra) are fused in a complex fashion to create 2∞[Ln19 Mn10 Te48 ] 19− layers. These structures do not contain any homoatomic bonding and hence, can be easily charge-balanced as (Cs 1+ )19 (Ln 3+ )19 (Mn 2+ )10 (Te 2− )48 as per the Zintl–Klemm concept. The optical absorption study on finely ground single crystals of the Gd-compound reveals a direct bandgap of about 0.5(1) eV. The DFT studies also suggest both systems to be semiconductors with bandgaps of ∼0.5 eV consistent with the experimental value.